Evaluation of Students' Knowledge and Attention or Concern using Learning Videos on Renewable Energy - Nugraini, Siti Hadiati; Nugroho, Yusro Edy (ANDHARUPA: Jurnal Desain Komunikasi Visual & Multimedia, 2023)
AbstractThis research describes the evaluation of students when learning videos on renewable energy to increase students' knowledge and awareness about reducing fossil energy. Learning models, namely learning videos and other features, support student learning processes. Some of the learning videos describe Biodiesel or renewable energy sources derived from vegetable resources, namely used cooking oil, which is one of the current crucial problems regarding reducing fossil energy that must be addressed immediately. Students, as the nation's young generation, are less concerned about this problem, so there is a need for a learning model about renewable energy that can increase student knowledge and concern about the current reduction in fossil energy. One alternative learning model to clarify this subject is through Renewable Energy themed Learning Videos in Audio Visual class. The research method used is a descriptive qualitative method and a quantitative method. Respondents in this study were 60 students from the Audio Visual subject group. The Learning Model fully uses Learning Videos. Evaluation of the impact of this learning model shows that, in fact, with this learning model, the knowledge and attention or concern of students increases after participating in the learning process using learning videos with the theme of renewable energy.  Keywords: evaluation, learning model, learning video, renewable energy AbstrakPenelitian ini mendeskripsikan hasil evaluasi siswa ketika mempelajari video energi terbarukan untuk meningkatkan pengetahuan dan kesadaran siswa tentang pengurangan energi fosil. Model pembelajaran yaitu video pembelajaran dan fitur lainnya mendukung proses belajar siswa. Beberapa video pembelajaran menjelaskan tentang Biodiesel atau sumber energi terbarukan yang berasal dari sumber daya nabati yaitu minyak jelantah yang merupakan salah satu permasalahan krusial saat ini terkait pengurangan energi fosil yang harus segera diatasi. Pelajar sebagai generasi muda bangsa kurang memperhatikan masalah ini, sehingga perlu adanya model pembelajaran tentang energi terbarukan yang dapat meningkatkan pengetahuan dan kepedulian siswa terhadap pengurangan energi fosil saat ini. Salah satu alternatif model pembelajaran untuk memperjelas mata kuliah ini adalah melalui Video Pembelajaran bertema Energi Terbarukan di kelas Audio Visual. Metode penelitian yang digunakan adalah metode kualitatif deskriptif dan metode kuantitatif. Responden dalam penelitian ini adalah 60 siswa dari kelompok mata pelajaran Audio Visual. Model pembelajaran sepenuhnya menggunakan video pembelajaran. Evaluasi dampak model pembelajaran ini menunjukkan bahwa sebenarnya dengan model pembelajaran ini pengetahuan dan perhatian atau kepedulian siswa meningkat setelah mengikuti proses pembelajaran menggunakan video pembelajaran bertema energi terbarukan. Keywords: evaluasi, energi terbarukan, model pembelajaran, video pembelajaran